Foreign language learning motivation in higher education: a longitudinal study on motivational changes and their causes - Busse, V (2010)
L2 motivational research may be described as an ongoing quest to identify motivational attributes underlying motivated language learning behaviour. This study employs a novel theoretical and methodological focus in this endeavour: firstly, it applies theories of the self to a motivational exploration of L2 motivation involving first-year students studying towards German degree courses at two major UK universities. Secondly, the study explicitly addresses the time- and context-sensitive nature of motivational attributes. While the majority of L2 motivational studies treat motivational attributes as static and rely heavily on one-off surveys, this study uses a longitudinal mixed-methods approach. Questionnaires were administered at the beginning and at the end of the academic year, and students were interviewed five times over the course of the academic year. Results suggest that the concept of integrative orientation in its traditional sense plays a minor role for these students. The concepts of the ideal L2 self and intrinsic motivation are better suited to capture these students’ motivation for studying German, and together with self-efficacy beliefs they offer a good basis for understanding students’ motivated engagement with language learning throughout the year. However, the data also reveal that considerable changes take place during the course of the year. Importantly, students’ intrinsic motivation significantly decreases and so do self-efficacy beliefs for speaking and listening, a trend concomitant with decreasing effort to engage with language learning. The qualitative data shed light on the motivational changes observed, and provide a detailed and rich picture of the interplay between motivation and contextual factors. Based on the empirical insights gained, a theoretical framework is proposed which links the motivational attributes examined and situates them within multilayered contextual spheres. The thesis concludes by outlining pedagogical suggestions how to counteract decreasing motivation during the first year at university.